The Correlation between Understanding the Independent Learning – Kampus Merdeka (MBKM) Curriculum with the Fulfilment of PAI Student Learning Rights - Mohamad Agung Rokhimawan; Muhammad Ghozil Aulia; Ikhsan Rifai; Azahro, Suci Luthfiah Azahro (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – The lack of information on the Merdeka Belajar and Kampus Merdeka (MBKM) curriculum has made students not take the MBKM programs. The study aims to determine to what extent the relation between PAI students' understanding of the Merdeka Belajar – Kampus Merdeka (MBKM) curriculum policy implemented at Islamic Religious Universities (PTKI) and the fulfillment of PAI students' learning rights. Design/methods/approach – The type of research used is quantitative research with a correlational survey design. Data collection was conducted using a questionnaire containing 49 questions, where all questions were validated and the results were reliable. From a population of 650 students from 15 PTKI, 152 Islamic religious education students were taken as respondents. The collected data was analyzed using simple linear regression analysis. Findings – The analysis results obtained a value of r = 0.932 and a significance value of 0.00 (p < 0.05). The R Square (R2) result was 0.869, showing that 86.9% of PAI students can understand the concept of the MBKM curriculum at PTKI well so that there is a decision-making relation to take the learning rights of PAI students. Research implications/limitations – This research is limited to understanding the concept of the MBKM curriculum. Therefore, further research is expected to reach the implementation stage of the MBKM curriculum. In addition, policymakers should consider expanding the implementation of Merdeka Curriculum programs to a broader scale. Originality/value – The study results have proved the PAI students' ability to understand the concept of the MBKM curriculum related to the fulfillment of their learning rights. Most PAI students can understand the basic concepts of the MBKM curriculum. However, there are still some PAI students who do not understand holistically, requiring treatment to improve their understanding of the MBKM curriculum concept.